2018
DOI: 10.4155/fmc-2017-0162
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Molecules in the Lung: Formulation Challenges and Future Directions for Innovation

Abstract: Inhaled antimicrobials have been extremely beneficial in treating respiratory infections, particularly chronic infections in a lung with cystic fibrosis. The pulmonary delivery of antibiotics has been demonstrated to improve treatment efficacy, reduce systemic side effects and, critically, reduce drug exposure to commensal bacteria compared with systemic administration, reducing selective pressure for antimicrobial resistance. This review will explore the specific challenges of pulmonary delivery of a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 177 publications
(204 reference statements)
0
10
0
Order By: Relevance
“…The market makes available some formulations of inhaled antibiotics, including tobramycin, colistin and aztreonan, which are mainly directed to the treatment of infections associated with cystic fibrosis conditions [66]. Other applications have been reported occasionally, such as the use of aerosolized antibiotics in hospital-acquired pneumonia [67].…”
Section: Delivery Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The market makes available some formulations of inhaled antibiotics, including tobramycin, colistin and aztreonan, which are mainly directed to the treatment of infections associated with cystic fibrosis conditions [66]. Other applications have been reported occasionally, such as the use of aerosolized antibiotics in hospital-acquired pneumonia [67].…”
Section: Delivery Of Antibioticsmentioning
confidence: 99%
“…Other applications have been reported occasionally, such as the use of aerosolized antibiotics in hospital-acquired pneumonia [67]. Research in the area has been increasing consistently, and a recent review on inhalable antibiotic formulations is available in [66]. Along with the discovery of new antibiotics, the development of delivery systems to improve the therapeutic performance of the molecules has been object of scientific efforts and both approaches are, in fact, effective countermeasures against antibiotic resistance.…”
Section: Delivery Of Antibioticsmentioning
confidence: 99%
“…The technology has been used in the TOBI Podhaler device (Novartis Pharmaceuticals, Basel, Switzerland), which is used for delivering tobramycin for the treatment of infections caused by Pseudomonas aeruginosa in patients with cystic fibrosis. Indeed, antimicrobial therapy is one area that has benefitted from extensive recent research and development in inhaled drug delivery to the lungs [48]. It offers the opportunity to achieve high doses of antibiotics directly at the site of infection, without requiring potentially toxic high systemic concentrations, reducing the number of cellular barriers that must be negotiated by the molecule before reaching the bacterial infection.…”
Section: What Are the Current Incentives Driving Inhaler Development mentioning
confidence: 99%
“…Lung concentrations up to 30 times higher than those measured following intravenous administration can be achieved by inhalation [49]. Besides tobramycin, formulations of colistin, aztreonam and levofloxacin have been approved for the treatment of lung infections in cystic fibrosis, and several other classes are in development [48]. …”
Section: What Are the Current Incentives Driving Inhaler Development mentioning
confidence: 99%
“…People with CF inhale antibiotics regularly as a chronic, suppressive therapy against persistent bacterial infection. This achieves high drug concentration at the site of infection (i.e., in the airway) without the high systemic exposure and associated risks of systemic side effects when administered enterally or intravenously (6). Prospective clinical trials and long-term observational studies have demonstrated relatively low risks of serious side effects from even years of intermittent inhaled antibiotic therapy, which is now the standard of care in the United States (7).…”
mentioning
confidence: 99%